Military leadership lessons for public service - Szypszak, Charles (McFarland & Company, Inc., Publishers, 2016)
"Military veterans have had some of the most intensive leadership training. Effective management of civil emergencies calls for the same official demeanor, decisiveness and trustworthiness as does combat. Good leadership is fundamentally the same in ordinary day-to-day challenges, as well. This book describes how the principles and methods of military leadership are effective for public service"--